Pengaruh Kualitas Pelayanan dan Kinerja Pegawai Terhadap Kepuasan Pemustaka Di Dinas Perpustakaan dan Kearsipan Kota Magelang - Namira, Fatya Artha; Nugraha, Joko Tri; Mali, Matheus Gratiano; Orbawati, Eny Boedi (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this study was to determine how much influence the quality of service and employee performance on library satisfaction at the Magelang City Library and Archives Office. The method used in this research is associative with a quantitative approach. The source of data in this study comes from respondents, namely users who visit the Library and Archives Office of Magelang City. The method used in this research is associative with quantitative approach. The source of data in this study came from respondents, namely users who visit the Library and Archives Office of Magelang City. Data analysis techniques used Descriptive Statistical Test, Classical Assumption Test, Multiple Linear Regression Analysis, and Hypothesis Test. The conclusions of the results of this study are: (1) Service Quality has a significant positive effect on Library Satisfaction with a value of 4.924 > 1.661. (2) Employee Performance has a significant positive effect on Library Satisfaction with a value of 2.179 > 1.661. (3) Service Quality and Employee Performance have a significant positive effect on Library Satisfaction with an influence value of 53.1%. That way, the value of Ha is accepted and Ho is rejected because service quality and employee performance have an influence on library satisfaction.